Experiências de co-maternidade homomaternal em mulheres lésbicas e bissexuais - Barbosa, Hanna Barbara de Andrade (2023)
The theme of the family has been constantly studied as it is a universal phenomenon, with these studies increasingly focusing on different family arrangements. Occurring in Brazil, since the last decades of the twentieth century, the scope of what is meant by family. This made it possible for same-sex families to gain more visibility, as well as social and legal legitimacy. However, a deletion is identified in the scientific productions in relation to these families’ experiences, when compared with the productions referring to families composed of a couple of parents. Thus, the present dissertation proposed to understand the experiences of same-sex motherhood from the desire and parental satisfaction, giving visibility to these families’ experiences in the Brazilian context. For this, two studies were carried out: An integrative review of the Portuguese and English literature on homo-maternal experiences in a co-maternity situation. And a second study, from a qualitative nature, which sought to investigate the homo-maternal experiences lived in a co-maternity situation by female couples in Brazil, with the aim of exploring the trajectories towards homo-maternity, the gestation process and, the experiences, prejudices and stereotypes that encompass these experiences. The specificities of same-sex motherhood are discussed, as well as the influences and impacts of heteronormativity on their experiences.